The structure of professionally focused training content Electrical future Mechanical Engineers - Lazarev, N; Mosienko, A.; Tarasenko, A. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the problem of structure formation of professionally focused training content for future electrical machine building engineers. A systematic approach to the formation of professionally focused content Electrical Training. The requirements for the content of teaching discipline, taking into account peculiarities of the sphere of professional activity as a mechanical engineer. The main components of the discipline, based on the analysis of professional activity of engineers, machine-building industry in the conditions of modern production, which is the basis of the content of professional training of future machine engineers. Of particular importance in the system of professionally-oriented training of future engineers is the maximum approximation of classical electrical engineering topics in the subject area and their transformation through the development of domain-specific content Electrical Engineering. The prospects of further professionalization of the discipline, the approach of theoretical propositions to the specific production requirements, filling idealized definitions of real physical content are determinate.